Kaizen, organizational profile and the competency level of seafood and talabahan restaurants in Villa, Iloilo City - Bones, Grapes; Olaer, Mae Grace; Ramos, Yvony Joy; Rojo, Lea; Taghap, Ralyn; Tunguia, Joy
The study examines the Kaizen, organizational profile, and the competency level of seafood and talabahan restaurants in Villa, Iloilo City. It also assesses the competency level based on the managers' and customers' perspective and looks at the importance of kaizen for the industry. The respondents of the study included seven managers and eighty customers. Qualitative descriptive analysis was made on the major variable of the study. Almost all industries conduct business to achieve common goals, which is usually to gain profits or earn assets as well as providing customers' satisfaction and delight. As a whole, seafood and talabahan restaurants in Villa, Iloilo City consider improvements and innovations to have a great significance and impact on the implementation of company's strategies and in providing more efficient and better services to customers. Yet those improvements are not continuously made and are usually done for some other purposes, just like replacement of older and damaged equipment, adaptation to different occasions, and the trend that is also used by some of their competitors that is also being demanded by the customers.Although they do not necessarily follow Kaizen, managers feel that this will not have a drastic impact on their competency level. On the other hand, these improvements are of utmost importance to most of the customers. With the current trend nowadays and with the increasing demands of the customers, it would be better if the managers/owners in this industry would have ample idea about Kaizen and how would this affect their operations, management and goals accomplishment. So far, seafood and talabahan restaurants in general have very good and excellent relationship with their customers and suppliers and the innovations done are one of the reasons why customers love to go and spend their eating experience in this restaurants. The accessibility of the place and the budget friendly meals also seem to be one of the considered gained value. These restaurants are also deemed to be patronized by people at any economic and occupational status. Their price list is usually indicated by the pulse of their competitors, most especially by large-scale restaurants in same industry. These small-scale seafood and talabahan restaurants do not have fixed allocated budget for certain innovations unlike those large ones. In order to compete with large-scale restaurants, Kaizen would really be a great help. However in the case of competition between small-scale seafood and talabahan restaurants, the effect of innovation and improvements doesn't show absolute and explicit effect on their competency level.